Prepositions in Modern Greek – Accusative or Genitive Case? - Baćić Ćosić, Maja G.; Rađenović, Anka M. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
Prepositions are indeclinable words with limited lexical meaning that cannot stand alone but can govern one or more cases. In Modern Greek, which has four cases (nominative, genitive, accusative, and vocative), prepositions are commonly used to express a variety of relations (such as location, time, direction, etc.). Specifically, certain prepositions in this language can be followed simultaneously by the accusative and genitive cases. The aim of this paper is to investigate how a group of students of Modern Greek as L2 at the Department of Modern Greek Studies, Faculty of Philology, University of Belgrade, perceive the use of prepositions that syntactically correspond to the accusative and the genitive and change their meaning depending on the case they are used with. A non-experimental quantitative survey with multiple-choice, closed-ended questions was conducted. Respondents were asked to form prepositional phrases with prepositions that can be followed by both genitive and accusative (επί, υπό, από, προς, μετά, and κατά) by choosing nouns in one of the above cases. This paper aims to identify the semantic and syntactic components that may be problematic for learners of Modern Greek as L2 in the use of prepositions and prepositional phrases, as well as to suggest strategies for more efficient acquisition and use of this word class in Modern Greek.